Ubiquilin‐1 immunoreactivity is concentrated on Hirano bodies and dystrophic neurites in Alzheimer's disease brains. Issue 7 (29th October 2013) - Satoh, J.; Tabunoki, H.; Ishida, T.; Saito, Y.; Arima, K.
Abstract : Aims: Ubiquilin‐1 acts as an adaptor protein that mediates the translocation of polyubiquitinated proteins to the proteasome for degradation. Although previous studies suggested a key role of ubiquilin‐1 in the pathogenesis of Alzheimer's disease (AD), a direct relationship between ubiquilin‐1 and Hirano bodies in AD brains remains unknown. Methods: By immunohistochemistry, we studied ubiquilin‐1 and ubiquilin‐2 expression in the frontal cortex and the hippocampus of six AD and 13 control cases. Results: Numerous Hirano bodies, accumulated in the hippocampal CA1 region of AD brains, expressed intense immunoreactivity for ubiquilin‐1. They were much less frequently found in control brains. However, Hirano bodies did not express a panel of markers for proteasome, autophagosome or pathogenic proteins, such as ubiquilin‐2, ubiquitin, p62, LC3, beclin‐1, HDAC6, paired helical filament (PHF)‐tau, protein‐disulphide isomerase (PDI) and phosphorylated TDP‐43, but some of them expressed C9orf72. Ubiquilin‐1‐immunoreactive deposits were classified into four distinct morphologies, such as rod‐shaped structures characteristic of Hirano bodies, dystrophic neurites contacting senile plaques, fragmented structures accumulated in the lesions affected with severe neuronal loss, and thread‐shaped structures located mainly in the molecular layer of the hippocampus. Conclusions: Ubiquilin‐1 immunoreactivity is concentrated on Hirano bodies and dystrophic neurites in AD brains, suggesting that aberrant expression of ubiquilin‐1 serves as one of pathological hallmarks of AD.